TEACHERS’ LESSON PLANS IN DIFFERENT SCHOOL LEVELS (A DESCRIPTIVE RESEARCH OF THREE DIFFERENT SCHOOL LEVELS) - Nadia Astarina, Atri (English Education Department of STKIP Pasundan, 2020)
Developing lesson plans which significantly influence the successful teaching learning process is not an easy thing for some teachers in three different school levels. It is because there are some influential aspects which should be considered in developing it. Thus, this research was conducted to investigate the aspects taken in developing lesson plan as well as to investigate whether there is any difference between the lesson plans developed for three different school levels. It employed qualitative method with descriptive design towards teacher of elementary school, junior high school, and senior high school. The data were obtained through document analysis and interview as the confirmation. There were 6 lesson plans gathered from 3 English teachers of different school levels. This research was analyzed using theories adapted from Reiser and Dick (1996) and Brown (2001). The research revealed that generally the aspects consisted in most of lesson plans analyzed were likely consistent with the theories proposed except in terms of coherence in using specific verbs stated in objectives and activities. In addition, it was revealed that there were no any significant differences between lesson plans developed for Elementary School, Junior High School, and Senior High School except in terms of Bloom’s ability level (1965) stated in objectives. Thus, further research might investigate how teachers can use more coherent specific verbs stated in objectives and activities to make the better lesson plans and teaching learning process.